DESIGNING EFFECTIVE ONLINE ADVERTISEMENTS FOR A PREVENTION CAMPAIGN: MISTRUST AND OTHER BARRIERS - Henry, Claire (AoIR Selected Papers of Internet Research, 2019)
This paper reports on the preliminary findings of a research project that is investigating the potential for online advertisements to reduce the incidence of Child Sexual Abuse Material (CSAM) consumption on the internet. First time or novice offenders often use search engines to look for CSAM, which presents an opportunity to use display advertisements (for a 24-hour sexual harm helpline) on search results for early intervention. This approach—currently being piloted in New Zealand—aims to decrease the number of potential/novice offenders accessing CSAM, and increase the number seeking help and self-referring for treatment. However, achieving these outcomes crucially depends upon the use of effective images and advertisements, and yet limited research has been undertaken on the characteristics of effective media-based interventions in this context. These outcomes also crucially depend on a two-way relationship of trust: on the one hand, the advertiser’s trust in primary prevention as a strategy, in the potential of online advertising to encourage behavioral change, and in the users’ likelihood of users self-referring contacting the helpline; and on the other hand, the users’ trust—or overcoming of mistrust—in both display advertising targeted at them and in the advertisers themselves (when engagement with both may involve overcoming fears about privacy, surveillance, prosecution, or stigmatization). This paper discusses the pivotal role of trust in informing the development of CSAM prevention display advertisements, arguing that facilitating this two-way relationship of trust is core to the success of a prevention campaign and must be embedded into its design.